Embedded trapped modes for water waves in an infinite channel - Rodríguez, M. I. Romero (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We present a simple perturbation scheme for calculating the frequencies of water waves trapped by a small obstruction of the water bed. The corresponding solutions describe embedded  trapped modes that are localized at the obstruction and decay at infinity. A simple formula for their frequencies is obtained.